An improved model of hybrid multi converter used for grid connected applications - E. Catherine Amala Priya; G. T. Sundar Rajan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
A Hybrid multi converter topology is proposed in this paper, which supplies simultaneous voltage’s for various levels from Renewable energy source. The proposed topology is realized by replacing Multi cuk- buck converter topology. The resultant hybrid multi converter requires less number of switches to operate, as well as various output voltages of different levels without interruption with increased stability. This type of hybrid multi converter with high reliability and high stability are well implemented for loads utilizing various levels of DC voltage. Converter, proposed in this paper is called Hybrid Multi converter topology (HMCT). A study is made on the steady state of the HMCT and a comparative study has been made with the conventional designs. A PI controller based feedback controller is designed to stabilize the various output voltages. A simulated model for the proposed HMCT is used to simulate various output voltages of dissimilar values from mono DC- input. The performance of the converter is demonstrated using simulation model. The proposed design can be protracted to voltage source inverter, multilevel inverter to produce AC output.